1990
DOI: 10.1152/jn.1990.64.2.509
|View full text |Cite
|
Sign up to set email alerts
|

Gaze control in the cat: studies and modeling of the coupling between orienting eye and head movements in different behavioral tasks

Abstract: 1. Orienting movements, consisting of coordinated eye and head displacements, direct the visual axis to the source of a sensory stimulus. A recent hypothesis suggests that the CNS may control gaze position (gaze = eye-relative-to-space = eye-relative-to-head + head-relative-to-space) by the use of a feedback circuit wherein an internally derived representation of gaze motor error drives both eye and head premotor circuits. In this paper we examine the effect of behavioral task on the individual and summed traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(131 citation statements)
references
References 62 publications
10
119
2
Order By: Relevance
“…Importantly, we also found that gaze remained accurate despite the head perturbations, even though the VOR was suppressed. These findings are compatible with a series of models that suggest that the brain uses feedback control of gaze trajectory, and not eye trajectory to change the line of sight (Laurutis and Robinson, 1986;Guitton and Volle, 1987;Pelisson et al, 1988;Guitton et al, 1990;Tomlinson, 1990;Lefèvre and Galiana, 1992;Goossens and Van Opstal, 1997;Daye et al, 2014). Our results imply further that the passively induced VOR is modulated by a gaze rather than an eye velocity signal.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Importantly, we also found that gaze remained accurate despite the head perturbations, even though the VOR was suppressed. These findings are compatible with a series of models that suggest that the brain uses feedback control of gaze trajectory, and not eye trajectory to change the line of sight (Laurutis and Robinson, 1986;Guitton and Volle, 1987;Pelisson et al, 1988;Guitton et al, 1990;Tomlinson, 1990;Lefèvre and Galiana, 1992;Goossens and Van Opstal, 1997;Daye et al, 2014). Our results imply further that the passively induced VOR is modulated by a gaze rather than an eye velocity signal.…”
Section: Introductionsupporting
confidence: 86%
“…Despite the modification of the saccade trajectory, the gaze ended on target, demonstrating feedback control that compensates for the perturbation. Two possibilities have been proposed for the control of head-free saccades: either the CNS controls the gaze trajectory with feedback (Laurutis and Robinson, 1986;Guitton and Volle, 1987;Pelisson et al, 1988;Guitton et al, 1990;Tomlinson, 1990;Lefèvre and Galiana, 1992;Goossens and Van Opstal, 1997;Daye et al, 2014), or it controls the eye and the head separately without gaze feedback (Freedman, 2001(Freedman, , 2008Freedman and Cecala, 2008;Kardamakis and Moschovakis, 2009;Kardamakis et al, 2010). A separate control of eye and head based on a prior decomposition of the gaze command, with no feedback of the gaze and an imperfect VOR, could not compensate for the head perturbation be- cause the eye controller would have no information about how the perturbation might have affected gaze.…”
Section: Discussionmentioning
confidence: 99%
“…The ¢ring rates of the tectoreticular spinal neurons (TR(S)Ns), which are found in the deep layers of the SC, are thought to encode gaze as opposed to eye or head movements alone (Munoz & Guitton 1991). Munoz & Guitton (1989) and Guitton et al (1990) discovered that the appearance of a visual target just prior to a gaze movement caused a sudden increase in the orientating TR(S)N discharge frequency and a modi¢cation in the acceleration of the subsequent gaze movement. This alteration in the acceleration of the gaze started ca.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was proposed, on the basis of gaze control studies in the cat, that both the oculomotor system and the head motor system are controlled by the same internally created gaze motor-error signal (Galiana and Guitton 1992; Guitton et al 1990). Several behavioural and neurophysiological studies provide support for this so-called common gaze model (reviewed by Guitton 1992).…”
Section: Eye-head Coordination Studiesmentioning
confidence: 99%
“…According to the common drive hypothesis, the eye and head are both controlled by the same oculocentric gazeerror command (Galiana and Guitton 1992; Guitton et al 1990). Thus, both motor systems are expected to move in similar directions throughout the gaze saccade.…”
Section: Different Eye and Head Motor Commandsmentioning
confidence: 99%